Research on the Static Thermal Degradation Law of Lubricating Grease for Wind Power Bearings - Heng Tian; Yan Liu; Yuqing Fan; Gaofeng Wang; Zhiwei Wang (Lubricants)
This research addresses the issue of lubricant performance degradation in the main shaft bearings of wind turbines. Through multi-temperature accelerated aging tests, the static thermal degradation patterns were elucidated, and an aging model was developed. Initially, 176 samples were prepared at temperatures of 80 °C, 100 °C, 120 °C, and 140 °C using the static thermal degradation method, with 44 samples at each temperature point. Subsequently, key parameters such as the quality change rate, penetration, oil separation rate, and evaporation amount of the lubricant were systematically measured. Ultimately, the mathematical aging model of the lubricant was derived by fitting the aging kinetics model. The results indicate that as aging time and temperature increase, the degradation characteristics of the lubricant, such as quality change rate, penetration, oil separation rate, and evaporation amount, exhibit discernible patterns. The mathematical aging model was successfully fitted, with the maximum deviation generally within 20% of the error margin, meeting the established criteria. This research provides a theoretical foundation for the establishment of a lubricant condition monitoring system in wind farms. Predicting the performance inflection point of the lubricant can effectively prevent unplanned bearing shutdowns resulting from lubrication failures, thereby offering significant engineering value in enhancing the operational reliability of wind turbine units.